Optimal Application Mapping on NoC Infrastructure using NSGA-II and MicroGA - da Silva, Marcus Vinicius Carvalho; Nedjah, Nadia; de Macedo Mourelle, Luiza (2009 International Conference on Intelligent Engineering Systems, 2009)
Network-on-chip (NoC) are considered the next generation of communication infrastructure, which will be omnipresent in most of industry, office and personal electronic systems. In the platform-based methodology, an application is implemented by a set of collaborating intellectual properties (IPs) blocks. In this paper, we use multi-objective evolutionary optimization to address the problem of mapping topologically pre-selected sets IPs, which constitute the set of optimal solutions that were found for the IP assignment problem, on the tiles of a mesh-based NoC. The IP mapping optimization is driven by the area occupied, execution time and power consumption.